Histological findings on jaw osteonecrosis associated with bisphosphonates (BONJ) or with radiotherapy (ORN) in humans. (1st November 2013) - Carmagnola, Daniela; Canciani, Elena; Sozzi, Davide; Biglioli, Federico; Moneghini, Laura; Dellavia, Claudia
Abstract: Objective. To describe the histological features of bone tissue harvested from patients affected by jaw osteonecrosis associated with bisphoshponates (BONJ) or with radiotherapy (ORN), in undecalcified ground sections. Materials and methods. Sixteen bone tissue samples from 14 patients with BONJ and two patients with ORN were processed in order to obtain both ground, undecalcified sections and decalcified sections. The sections underwent histometric and morphometric analysis. Results. Bone tissue samples obtained from patients with BONJ or ORN of the jaws shared some histological characteristics. Common histological features included the loss of bone architecture, the absence of a proper Haversian system and proper marrow spaces, the presence of necrotic spots of non-mineralized tissue, areas of empty osteocytic lacunae next to areas of hypercellularity, the presence of resorption pits with rare osteoclast-like cells and the presence of bacteria and of an inflammatory infiltrate. A violet rib of tissue characterized by large resorption pits facing was frequently observed between the mineralized bone and the inflammatory infiltrate. Conclusions. The histological features of BONJ and ORN are similar and resemble those of osteomyelitis. Even though it is not clear whether infection is the cause or consequence of bone exposure, inflammatory cells, bacteria or their products may have a massive, direct lytic effect on bone tissue challenged by bisphosphonates.